The effect of different compression force on image quality and dose in full field digital mammography / Husna Syafina Mohd Taib, Hairenanorashikin Sharip - Sharip, Hairenanorashikin; Mohd Taib, Husna Syafina (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Breast compression is necessary and important in mammography to improve image quality and minimize the radiation given to the breast. However, the downsides of applying breast compression during mammography are pain and discomfort experienced by patients. This experimental study was carried out to investigate the effect of applying different compression force (Newton, N) of 30N, 45N and 60N on image quality and dose in Full Field Digital Mammography (FFDM). The study was done at Pantai Hospital Kuala Lumpur using Siemens Mammamot Inspiration FFDM. A set of CIRS012A breast phantom (4cm compressed thickness) was used as subject. TLD chips were used as dose measurement tool. Exposures were taken using Automatic Exposure Control (AEC) with fixed 28kVp and Tungsten/Rhodium (W/Rh) anode filter combination in only cranio-caudal (CC) projection. Criteria of image quality scoring were adapted from ACR Mammography Quality Control. Two experienced radiographers with at least 10 years of working experience in mammography scored the image independently. Analysis of variance (ANOVA) showed no significant difference between compression force and dose (p=0.296), and no significant difference between compression force and image quality (p=0.702). Pearson's Correlation showed no significant relationship between compression force and dose (r=0.289, p=0.451) and no significant relationship between compression force and image quality (r=0.01, p=0.91). In conclusion, applying different compression force does not significantly affect the image quality and dose in FFDM.